Flavonoids improve the stability and function of P23H rhodopsin slowing down the progression of retinitis pigmentosa in mice - Ortega, Joseph Thomas; Parmar, Tanu; Carmena‐Bargueño, Miguel; Pérez‐Sánchez, Horacio; Jastrzebska, Beata (Journal of neuroscience research, 2022)
The balanced homeostasis of the G protein–coupled receptor (GPCR), rhodopsin (Rho), is required for vision. Misfolding mutations in Rho cause photoreceptor death, leading to retinitis pigmentosa (RP) and consequently blindness. With no cure currently available, the development of efficient therapy for RP is an urgent need. Pharmacological supplementation with molecular chaperones, including flavonoids, improves stability, folding, and membrane targeting of the RP Rho mutants in vitro. Thus, we hypothesized that flavonoids by binding to P23H Rho and enhancing its conformational stability could mitigate detrimental effects of this mutation on retinal health. In this work, we evaluated the pharmacological potential of two model flavonoids, quercetin and myricetin, by using in silico, in vitro, and in vivo models of P23H Rho. Our computational analysis showed that quercetin could interact within the orthosteric binding pocket of P23H Rho and shift the conformation of its N‐terminal loop toward the wild type (WT)‐like state. Quercetin added to the NIH‐3T3 cells stably expressing P23H Rho increased the stability of this receptor and improved its function. Systemic administration of quercetin to P23H Rho knock‐in mice substantially improved retinal morphology and function, which was associated with an increase in levels of Rho and cone opsins. In addition, treatment with quercetin resulted in downregulation of the UPR signaling and oxidative stress‐related markers. This study unravels the pharmacological potential of quercetin to slow down the progression of photoreceptor death in Rho‐related RP and highlights its prospective as a lead compound to develop a novel therapeutic remedy to counter RP pathology. Flavonoids slow down the death of photoreceptors in retinitis pigmentosa caused by the P23H rhodopsin mutation by stabilizing the structural conformation of the receptor mutant and decreasing the cellular stress response.